2020
DOI: 10.29252/iem.6.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic and Microscopic Survey of the Comparative Effects of Lactobacillus plantarum 299v, Its Supernatant, and Imipenem on Infectious Burn Wound Healing in Rats

Abstract: Burn infections are one of the most common causes of mortality in the world. On the other hand, microbial resistance to antibiotics has caused concern in the medical community. Therefore, controlling burn infections is very important, and using alternative therapies instead of antibiotics could be a good solution to this problem. Materials & Methods: Lactobacillus plantarum 299v strains were used in the experiments. Fifty male Wistar rats were prepared, and burn was induced in animals. The burn wounds were ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In this regard, Venosi et al found that probiotic therapy has an inhibitory effect against Gram-positive and Gram-negative bacteria ( 25 ). Many studies have reported that the extracellular products of Lactobacillus spp have significant inhibitory activities against clinical isolates ( 17 ). The CFS of Lactobacillus spp contains antibacterial agents such as lipoteichoic acid, acetic acid, diacetyl, lactic acid, and hydrogen peroxide ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Venosi et al found that probiotic therapy has an inhibitory effect against Gram-positive and Gram-negative bacteria ( 25 ). Many studies have reported that the extracellular products of Lactobacillus spp have significant inhibitory activities against clinical isolates ( 17 ). The CFS of Lactobacillus spp contains antibacterial agents such as lipoteichoic acid, acetic acid, diacetyl, lactic acid, and hydrogen peroxide ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…To prepare probiotics CFS, Lactobacillus strains were cultivated in tubes containing MRS broth medium (MERCK, Germany) under microaerophilic conditions at 37°C for 24 h. The tubes were centrifuged (Sigma 3-16 k, Germany) at 10,000 g at 4°C for 30 min. Then, the supernatant was filtered through 0.22 μm filters (Millipore, Bedford, MA) ( 17 ).…”
Section: Methodsmentioning
confidence: 99%